Performance and determination of Concentration Ratio for a parabolic solar concentrator using a thermographic technique (2021)
ABSTRACT : This work addresses the methodology to determine the exact concentration ratio (CR) for a parabolic solar concentrator (PSC) using thermographic imaging. The value of CR is commonly given in terms of the area of the receiver and not in terms of the area of the image produced by the concentrator on the receiver surface. With thermographic analysis, it is possible to know the real image generated by the PSC on the receiver, which helps to have a precise calculation of CR. It is important to measure the real CR not only for manufacturing purposes but also for the maintenance of solar concentrators, since its miscalculation lowers their energy efficiency or lifespan. In experiments, the real image on the receiver is divided into 4 regions, stratified with an equal temperature difference for each one. With this consideration, CR varied from 20 to 151. To complete the analysis, the energy efficiency is calculated. Since heating is a non-stationary process, thermal efficiency fluctuated during the time of experimentation, having a peak of 25% and a mean value of 15.3%. The irregularities of curvature in the concentrators significantly deteriorate the uniformity of the radiation flux and the energy efficiency due to unused areas of concentration.